PEMANFAATAN DIMETHYL ETHER (DME) SEBAGAI SUBSTITUSI BAHAN BAKAR MINYAK DAN LPG - Mohamad Sidik Boedoyo (Jurnal Teknologi Lingkungan, 2010)
As a developing country, currently the energy demand in Indonesia increases rapidly.Although Indonesia has a huge of oil reserves the production of oil fuels as the main energy consumption has not been enough and should be imported. It is devised to substitute oil fuel with other resources such as liquefied coal, natural gas, biofuels and dimethyl ether (DME). In the short future, the use of DME as an alternative fuel appears to be a promising approach for reducing the uses of diesel oil and LPG. It can be described in to two approaches. First, due to the high cetane number of DME, it can be used for compression ignition engines which have higher thermal efficiencies compared to spark ignition engines. Second, due to the physical properties of DME, it can substitute oil fuels and LPG uses in industries, commercials, and households for lighting and cooking. Hence, DME production is not limited to one feedstock. DME canbe derived from fossil fuel feedstocks, including natural gas and coal, as well as from renewable feedstock sources such as biomass. Since Indonesia have abundant of energy sources as DME raw material, such as natural gas, coal and biomass, utilization of DME into Indonesia energy system is necessary to be developed.Key words :Energy Potential, Dimethyl Ether, Diesel Oil and LPG Substitution